Pengaruh Pemberian Ekstrak Etanol Daun Kelor (Moringa oleifera) Terhadap Gambaran Histologi Hepar pada Tikus Putih (Rattus norvegicus) yang Dipapar Alkohol - Marselina Marselina; Hudi Winarso; Olivia Tantana (Dinasti Research, 2023)
Liver damage continues to be a prevailing global health issue. Primary risk factors to liver impairment encompass excessive alcohol consumption. According to the National Anti-Alcohol Movement in 2014, it was disclosed that 23% of 14.4 million adolescents in Indonesia consumed alcohol, indicating a substantial increase compared to 2007. With the progression of scientific knowledge, herbal plants such as Moringa oleifera leaves have been extensively utilized for medicinal purposes due to their content of phytochemical compounds like flavonoids, glucosinolates, isothiocyanates, and phenolic acids, which play crucial roles as antioxidants and anti-inflammatory agents. The aim of this research is to examine the influence of ethanol extract from Moringa oleifera leaves on the histological depiction of the livers of white rats (Rattus norvegicus) exposed to alcohol. The research method involved 25 rats divided into five groups, each consisting of 5 rats. The negative control group (K-) received standard feed and water, the positive control group (K+) received 25% alcohol, and three other groups received 25% alcohol along with Moringa oleifera leaf extract at three different doses (250 mg/kgBW, 500 mg/kgBW, and 1000 mg/kgBW) for 21 days. The research findings highlight a significant disparity in terms of necrotic cells, with K+ displaying 22.4 hepatocyte necrosis, K1 with 20.8 hepatocyte necrosis, K2 with 13.2 hepatocyte necrosis, and K3 with 6.2 hepatocyte necrosis. The K+ and K1 groups experienced more substantial hepatic damage compared to the K-, K2, and K3 groups. Meaningful improvements were notably evident, especially in the treatment group receiving Moringa oleifera leaf extract at a dose of 1000 mg/kgBW, indicating the involvement of the dose of Moringa oleifera leaf extract as a factor influencing the level of hepatocyte cell recovery.